Correlation of gas dynamics and dust in the evolved filament G82.65-02.00 - M. Saajasto; M. Juvela; K. Dobashi; T. Shimoikura; I. Ristorcelli; J. Montillaud; D. J. Marshall; J. Malinen; V.-M. Pelkonen; O. Fehér; A. Rivera-Ingraham; L. V. Toth; et al. (EDP SCIENCES S A, 2022)
Context. The combination of line and continuum observations can provide vital insight into the formation and fragmentation of filaments and the initial conditions for star formation. We have carried out line observations to map the kinematics of an evolved, actively star forming filament G82.65-2.00. The filament was first identified from the Planck data as a region of particularly cold dust emission and was mapped at 100-500 mu m as a part of the Herschel key program Galactic Cold Cores. The Herschel observations cover the central part of the filament, corresponding to a filament length of similar to 12 pc at the assumed distance of 620 pc.& para;& para;Aims. CO observations show that the filament has an intriguing velocity field with several velocity components around the filament. In this paper, we study the velocity structure in detail, to quantify possible mass accretion rate onto the filament, and study the masses of the cold cores located in the filament.& para;& para;Methods. We have carried out line observations of several molecules, including CO isotopologues, HCO+, HCN, and CS with the Osaka 1.85 m telescope and the Nobeyama 45 m telescope. The spectral line data are used to derive velocity and column density information.& para;& para;Results. The observations reveal several velocity components in the field, with strongest line emission concentrated to velocity range similar to[3,5] km s(-1). The column density of molecular hydrogen along the filament varies from 1.0 to 2.3 x 10(22) cm(2). We have examined six cold clumps from the central part of the filament. The clumps have masses in the range 10-20 M circle dot (similar to 70 M circle dot in total) and are close to or above the virial mass. Furthermore, the main filament is heavily fragmented and most of the substructures have a mass lower than or close to the virial mass, suggesting that the filament is dispersing as a whole. Position-velocity maps of (CO)-C-12 and (CO)-C-13 lines indicate that at least one of the striations is kinematically connected to two of the clumps, potentially indicating mass accretion from the striation onto the main filament. We tentatively estimate the accretion rate to be M = 2.23 x 10(-6) M circle dot/yr.& para;& para;Conclusions. Our line observations have revealed two or possibly three velocity components connected to the filament G82.65-2.00 and putative signs of mass accretion onto the filament. The line observations combined with Herschel and WISE maps suggest a possible collision between two cloud components.